2012
DOI: 10.1104/pp.112.195446
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin Redox Regulates ATPase Activity of Magnesium Chelatase CHLI Subunit and Modulates Redox-Mediated Signaling in Tetrapyrrole Biosynthesis and Homeostasis of Reactive Oxygen Species in Pea Plants      

Abstract: The chloroplast thioredoxins (TRXs) function as messengers of redox signals from ferredoxin to target enzymes. In this work, we studied the regulatory impact of pea (Pisum sativum) TRX-F on the magnesium (Mg) chelatase CHLI subunit and the enzymatic activation of Mg chelatase in vitro and in vivo. In vitro, reduced TRX-F activated the ATPase activity of pea CHLI and enhanced the activity of Mg chelatase reconstituted from the three recombinant subunits CHLI, CHLD, and CHLH in combination with the regulator pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
82
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(92 citation statements)
references
References 67 publications
10
82
0
Order By: Relevance
“…The findings are consistent with the previous observation in CHLI-silenced transgenic tobacco plants [26]. The silencing of Thioredoxin-F and M, which interact with and support the enzymatic activity of CHLI, resulted in the reduced expression of CPRGs and the chlorotic phenotype in pea plants [18]. Although the evidence is indirect in this case, it may support the idea that the downregulation of CHLI gives rise to the reduced expression of CPRGs.…”
Section: Discussionsupporting
confidence: 82%
“…The findings are consistent with the previous observation in CHLI-silenced transgenic tobacco plants [26]. The silencing of Thioredoxin-F and M, which interact with and support the enzymatic activity of CHLI, resulted in the reduced expression of CPRGs and the chlorotic phenotype in pea plants [18]. Although the evidence is indirect in this case, it may support the idea that the downregulation of CHLI gives rise to the reduced expression of CPRGs.…”
Section: Discussionsupporting
confidence: 82%
“…Nevertheless, the specific regulatory function of NTRC has remained elusive, because NTRC targets reported to date largely overlap with Trx targets (11). Although there are a few comparative studies addressing the functional difference between NTRC and specific Trx subtypes (16,(32)(33)(34), the results are partly inconsistent and, thereby, insufficient to verify distinct roles for NTRC from those for the Trx family.…”
Section: Ntrc and Five Trx Subtypes Differentially Recognize Target Pmentioning
confidence: 74%
“…However, given the Trx ability to reduce CHLI in vitro (Fig. 2 E and F) (22) and the physical interaction between Trx-f and CHLI in vivo (33), the FTR/Trx pathway is thought to contribute to CHLI redox regulation possibly in a redundant manner. It is highly plausible that the severely chlorotic phenotype of ftrb ntrc is a consequence of disrupted redox regulation of chlorophyll biosynthesis via both the FTR/Trx and NTRC pathways.…”
Section: Cooperative Redox Regulation By the Ftr/trx And Ntrc Pathwaymentioning
confidence: 99%
“…Moreover, in vivo experiment by Luo et al demonstrated that one class of chloroplast Trx, named asTrx-M can compensate a lack of different class of chloroplast Trx, named as Trx-F. Both Trxs act as of important redox regulators of Mg-chelatase (Luo et al 2012).…”
Section: Thioredoxin Systemmentioning
confidence: 99%